The Spirit of Implementation of Islamic Sharia in Aceh on the Protection of Women (Case Study in West Aceh District, Bireun and Lhoksemawe City) - Husaini Husda; Bustami Abubakar; Nuraini A. Manan; Nurrahmi Nurrahmi (Budapest International Research and Critics University, 2022)
This paper aims to reconstruct the image of a just society towards the application of Islamic law in Aceh in various existing regulations, both qanuns, regulations, instructions and appeals. So far, mage has been built through unbalanced research, especially those carried out by supporters of gender equality and human rights in their various studies which always state that women are restrained, marginalized and not given sufficient space in the domestic and public spheres. The research that has been exposed so far has only seen the views of feminists, gender and human rights observers, while academics, ulama, policy makers (executive-legislative) and women